2022
DOI: 10.1111/cns.14065
|View full text |Cite
|
Sign up to set email alerts
|

Motor network reorganization after motor imagery training in stroke patients with moderate to severe upper limb impairment

Abstract: Background: Motor imagery training (MIT) has been widely used to improve hemiplegic upper limb function in stroke rehabilitation. The effectiveness of MIT is associated with the functional neuroplasticity of the motor network. Currently, brain activation and connectivity changes related to the motor recovery process after MIT are not well understood.Aim: We aimed to investigate the neural mechanisms of MIT in stroke rehabilitation through a longitudinal intervention study design with task-based functional magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…All participants had a history of diagnosed stroke and were aged between 30 and 77 years. One study examined participants with a mean age of 30.9–39.8 years [ 56 ], 14 studies of 52.5–62.6 years [ 55 , 58 , 59 , 76 , 78 , 80 , 82 84 , 87 , 88 , 90 , 92 , 94 ], six of 64.0–67.6 years [ 57 , 77 , 81 , 85 , 86 , 91 ], and three of 70.7–77.7 years [ 79 , 89 , 93 ]. A total of 357 women and 532 men were studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants had a history of diagnosed stroke and were aged between 30 and 77 years. One study examined participants with a mean age of 30.9–39.8 years [ 56 ], 14 studies of 52.5–62.6 years [ 55 , 58 , 59 , 76 , 78 , 80 , 82 84 , 87 , 88 , 90 , 92 , 94 ], six of 64.0–67.6 years [ 57 , 77 , 81 , 85 , 86 , 91 ], and three of 70.7–77.7 years [ 79 , 89 , 93 ]. A total of 357 women and 532 men were studied.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 357 women and 532 men were studied. One study considered one woman and 28 men [ 92 ] and another five women and 25 men [ 76 ]. All other studies had a more balanced female-to-male ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies have con rmed the functional connectivity between the primary motor cortex (M1), primary sensory cortex (S1) and dorsolateral prefrontal cortex (DLPFC). The coactivation of M1 and S1 and DLPFC in planning, execution and control of movement has been well established [22][23][24]. In addition to the three brain regions mentioned above, recent studies have shown that cerebellar (CB) tACS can lead to improved cortical excitability and motor behavior [25], which affects balance and gait, limb movement, oculomotor control, and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no effective treatment for pediatric CSCI. Currently, motor imagery (MI) is being studied as a potential treatment for the functional recovery of motor dysfunction diseases 5,6 because it can activate sensorimotor networks and can be performed by injured patients who are unable to move voluntarily. [7][8][9] MI is the mental simulation of a movement in the absence of obvious motor output.…”
mentioning
confidence: 99%